(untitled) (Journal of Science, Technology and Innovation Policy, 2023)
This paper aims to describe the general overview of procurement practices at the Ministry of Defence, Malaysia. Although the Ministry’s procurement practices must align with the general public procurement guidelines, rules and regulations set up by the Ministry of Finance, defence procurement deals with highly diversified asset acquisitions which can be extremely complex and sensitive in nature, process, and regulations. As such, it is crucial to examine the current defence procurement practices in Malaysia from the perspective of two policy documents namely the National Defence Policy and the Defence White Paper. Brief discussions on the types of procurement and agencies involved in the procurement process are also presented. Previous studies related to defence procurement both from Western literature and local studies are also offered along with a brief view on the notion of value for money.